Coping with the Crisis : Policy Options for Emerging Market Countries - Crowe, Christopher (IMF Staff Position Notes; Staff Position Note ;, 2009)
This chapter outlines policies to help solve the debt overhang and bring about recovery in both groups of countries. The current financial turmoil is confronting emerging market economies with two shocks: a 'sudden stop' of capital inflows resulting from the global deleveraging process, and a collapse in export demand associated with the global slump. A key ingredient appears to be greater official financing to expand the 'policy space' available to emerging market economies (EME) to pursue supportive macroeconomic policies-including, in countries with large debt overhangs, by helping to meet the fiscal outlays associated with the resolution of that overhang. An important first step is to ensure an adequate framework to facilitate rapid debt workouts. Debt restructuring mechanisms can provide greater scope for monetary easing by reducing the negative repercussions of exchange rate depreciation on unhedged balance sheets. Depending on the available fiscal space, expansionary fiscal policy should also be deployed to support economic activity.